2005
DOI: 10.1016/j.femsec.2005.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the inoculant strain Pseudomonas putida KT2442 (pNF142) and of naphthalene contamination on the soil bacterial community

Abstract: The naphthalene-degrading activity of a Pseudomonas sp. strain isolated from a creosote-contaminated soil was shown to be encoded by the IncP9 plasmid pNF142 by transfer to Pseudomonas putida KT2442. The effects of the inoculant strain KT2442 (pNF142) and of naphthalene contamination on the soil bacterial community were studied in microcosms with the following treatments: (I) soil, (II) soil with naphthalene, (III) soil with naphthalene and inoculated with KT2442 (pNF142). The inoculant became the dominant bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 32 publications
3
75
0
3
Order By: Relevance
“…Langworthy et al (1998) found that high PAH concentrations increased the frequencies of nahA and alkB genes. Gomes et al (2005) also reported a positive correlation between naphthalene contamination and abundance of phnAc genes. The increase of these functional genes might be due to the natural selection of organisms capable of utilizing hydrocarbon compounds.…”
Section: Discussionmentioning
confidence: 88%
“…Langworthy et al (1998) found that high PAH concentrations increased the frequencies of nahA and alkB genes. Gomes et al (2005) also reported a positive correlation between naphthalene contamination and abundance of phnAc genes. The increase of these functional genes might be due to the natural selection of organisms capable of utilizing hydrocarbon compounds.…”
Section: Discussionmentioning
confidence: 88%
“…DGGE of the 16S rRNA gene amplicons was performed according to Gomes et al [31]. The gel was silver-stained according to Heuer et al [32].…”
Section: Pcr Amplification Of 16s Rrna Gene Fragments and Dgge Analysismentioning
confidence: 99%
“…Pseudomonas is a genus of high biotechnological interest and the capacity of this group for the degradation of xenobiotics is widely documented in the literature [5,6,24,32,35,37,43]. A previous study conducted in Ria de Aveiro showed that Pseudomonads represent 34.5% of the culturable fraction of naphthalene-degrading bacterioneuston of the SML of the Ria de Aveiro [14].…”
Section: Pseudomonads Among Surfactant-resistant Bacterioneuston Isolmentioning
confidence: 99%